2017
DOI: 10.1056/nejmoa1612348
|View full text |Cite
|
Sign up to set email alerts
|

Tight Glycemic Control in Critically Ill Children

Abstract: BACKGROUND In multicenter studies, tight glycemic control targeting a normal blood glucose level has not been shown to improve outcomes in critically ill adults or children after cardiac surgery. Studies involving critically ill children who have not undergone cardiac surgery are lacking. METHODS In a 35-center trial, we randomly assigned critically ill children with confirmed hyperglycemia (excluding patients who had undergone cardiac surgery) to one of two ranges of glycemic control: 80 to 110 mg per decil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 36 publications
4
128
0
5
Order By: Relevance
“…Some interviewees referred to risks related to hyperglycaemia, and there is some evidence that admission hyperglycaemia in critically ill children is associated with increased mortality [2830]. While tight glycaemic control has been practiced in intensive care units with the assumption that hyperglycaemia in the critically ill worsens outcomes, recent studies have shown no difference in mortality or morbidity between severely sick children assigned to a higher or lower target group [3133]. Although there is little evidence that dangerous hyperglycaemia or poor outcomes result from treating hypoglycaemia, hyperglycaemia, as well as recurrent hypoglycaemia, may be common after dextrose infusions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some interviewees referred to risks related to hyperglycaemia, and there is some evidence that admission hyperglycaemia in critically ill children is associated with increased mortality [2830]. While tight glycaemic control has been practiced in intensive care units with the assumption that hyperglycaemia in the critically ill worsens outcomes, recent studies have shown no difference in mortality or morbidity between severely sick children assigned to a higher or lower target group [3133]. Although there is little evidence that dangerous hyperglycaemia or poor outcomes result from treating hypoglycaemia, hyperglycaemia, as well as recurrent hypoglycaemia, may be common after dextrose infusions [34].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of tight glycemic control (TGC) in critically ill children continue to be studied. Multicenter studies have shown that TGC is associated with higher rates of health care associated infections and severe hypoglycemia in critically ill children; others suggest TGC has no significant impact on major clinical outcomes . The landmark NICE‐SUGAR trial demonstrated an increase in mortality among critically ill adults randomized to intensive glucose control (81‐108 mg/dL) compared with conventional glucose control (<180 mg/dL) .…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Because the NICE SUGAR study did not involve children, Agus et al [35] performed a randomized controlled trial of aggressive insulin treatment of hyperglycemia in pediatric patients in intensive care. This was not a study of pediatric sepsis, specifically, but many enrolled patients had infection and sepsis.…”
Section: Elevated Blood Sugarmentioning
confidence: 99%
“…This was not a study of pediatric sepsis, specifically, but many enrolled patients had infection and sepsis. Agus et al [35] enrolled 713 critically ill children and randomly assigned them to a lower target blood sugar group who received more insulin and to a higher target group who received less insulin. The main outcome measure, ICU-free days up to day 28, was similar in both groups.…”
Section: Elevated Blood Sugarmentioning
confidence: 99%